Przesłanki materialnoprawne dochodzenia roszczenia regresowego przez podmiot odpowiedzialny w stosunku do funkcjonariusza publicznego na gruncie ustawy o odpowiedzialności majątkowej funkcjonariuszy publicznych za rażące naruszenie prawa - Kuźmicka-Sulikowska, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article addresses the conditions that must be fulfilled in order for a liable entity e.g. the State Treasury which has paid damages to an aggrieved party for damage caused as a result of the action or omission of a public official to then pursue a recourse claim against the responsible official. The deliberations are centered around issues of material regulations. The analyses conducted demonstrate discrepancies between the conditions for liability of a liable entity compared to those of recourse liability of a public official towards that entity. It is then demonstrated that the potential for pursuing recourse claims against a public official is in fact quite limited.
Keywords: civil liability; material liability; public official; gross violation of the law; recourse claim